Remarkable effect of Fe and Se composition on magnetic properties-comparative study of the Fe-Se system at the nanoscale - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2022)
Herein, for the first time, the correlation between the phase structure and the magnetic properties of the Fe-Se system has been presented for FexSey compounds-where x/y ranges from 1:2 to 1:1. These phases-orthorhombic (FeSe2), monoclinic (Fe3Se4), hexagonal (Fe7Se8), and tetragonal (beta-FeSe)-were synthesized using a one-pot thermal decomposition route at the nanoscale. The magnetic properties vary enormously with change in the Fe/Se ratio due to the change in the Fe2+/Fe3+ ratio, crystal field environment around the Fe ions, magnetocrystalline anisotropy, Fe vacancies, and so forth. Among the four Fe-Se phases studied, two of them, Fe3Se4 and Fe7Se8, are ferrimagnetic below similar to 300 K and show semihard magnetic properties. The other two phases FeSe2 and beta-FeSe exhibiting weaker magnetism are less known for their magnetic properties. All these phases are prone to surface oxidation despite surface passivation, and its effect on the magnetic moment will be pronounced for the phases with weak magnetization such as FeSe2 and beta-FeSe.